Layanan Prima menuju ”Quality Tourism” Bali - Nurjaya, I Wayan; Solihin, Solihin; Kanca, I Nyoman (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Increasingly competitive competition among tourist accommodation providers, encourage the star hotel management and villas in Kuta to provide special services to their guests. In fact, such kind of services will lead to a concept of tourism called ”quality tourism”. This paper is a qualitative research. Its data collection was done through document study, observation, and in-depth interviews with 11 informants, consisting of five villas’s star hotel liners, three hotel and villa’s guests, and three observers of Bali tourism business. The result of the study shows that the excellent services to the guests provided by villa and hotel management in Kuta is the implementation of the concept of sapta pesona, done at the stage of pre-arrival service, reception service, housekeeping service, and food & bevarage. The impact of this excellent services gives tourist loyalty and revisit, reinforces the positive image of Bali tourism, and supports the sustainability of accommodation services and tourism business. In general, the excellent services for hotel and villa guests in Kuta has supported the efforts to realize the quality tourism in Bali. Innovations to improve the quality of service for hotel and villa guests are needed according to the development and demands of the tourism market.